Diel activity and variability in habitat use of white sea bream in a temperate marine protected area. (May 2016) - Di Lorenzo, Manfredi; Fernández, Tomás Vega; Badalamenti, Fabio; Guidetti, Paolo; Starr, Richard M.; Giacalone, Vincenzo Maximiliano; Di Franco, Antonio; D'Anna, Giovanni
Abstract: Fish populations are often comprised of individuals that use habitats and associated resources in different ways. We placed sonic transmitters in, and tracked movements of, white sea bream ( Diplodus sargus sargus ) in the no-take zone of a Mediterranean marine protected area: the Torre Guaceto marine protected area, (Adriatic Sea, Italy). Tagged fish displayed three types of diel activity patterns in three different habitats: sand, rocky reefs and "matte" of the seagrass Posidonia oceanica . Individuals were more active during the day than at night. Overall, white sea bream displayed a remarkable behavioural plasticity in habitat use. Our results indicate that the observed behavioural plasticity in the marine protected area could be the result of multiple ecological and environmental drivers such as size, sex and increased intra-specific competition. Our findings support the view that habitat diversity helps support high densities of fishes. Highlights: We investigated patterns of movement of white sea bream living in a no-take zone. Tracked individual displayed three different types of diel activity patterns and habitat use. This behavioural plasticity could be a result of intra-specific competition.